Isaiah 3:16–23: Dress, pride, ostentatious items or syncretism? - Paul Nyarko-Mensah; Dirk J. Human (Verbum et Ecclesia)
The study investigated Isaiah 3:16–23 using the historical-grammatical methodology for the following reasons: to explore the author’s aim in writing the passage, ascertain the socio-psychological significance of dress and outward appearance, determine whether the items listed are exclusively female dresses and examine the contribution of the women of Zion to national sin. Does the passage prohibit the use of jewellery? Isaiah rebuked the women for their pride in appearance, suggesting that their sin was a haughty spirit, expressed through their manner of walking and the use of luxurious items. The items listed include both male and female articles of dress and are not exclusively female dresses. Also, the list included items which had their origin in the cult and magic system of their Canaanite neighbours. Outward appearance can reflect one’s socio-economic status, as well as religious, moral and cultural values. Dress can influence how a person is perceived by others and can also affect one’s values.